Microbial Community Dynamics during the Bioremediation Process of Chlorimuron-Ethyl-Contaminated Soil by Hansschlegelia sp. Strain CHL1 - Yang, Liqiang (PLoS One, 2015)
Long-term and excessive application of chlorimuron-ethyl has led to a series of environmental problems. Strain Hansschlegelia sp. CHL1, a highly efficient chlorimuron-ethyl degrading bacterium isolated in our previous study, was employed in the current soil bioremediation study. The residues of chlorimuron-ethyl in soils were detected, and the changes of soil microbial communities were investigated by phospholipid fatty acid (PLFA) analysis. The results showed that strain CHL1 exhibited significant chlorimuron-ethyl degradation ability at wide range of concentrations between 10μg kg(-1) and 1000μg kg(-1). High concentrations of chlorimuron-ethyl significantly decreased the total concentration of PLFAs and the Shannon-Wiener indices and increased the stress level of microbes in soils. The inoculation with strain CHL1, however, reduced the inhibition on soil microbes caused by chlorimuron-ethyl. The results demonstrated that strain CHL1 is effective in the remediation of chlorimuron-ethyl-contaminated soil, and has the potential to remediate chlorimuron-ethyl contaminated soils in situ.